2009
DOI: 10.1111/j.1476-5381.2009.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential inhibitory effects of drugs acting at the noradrenaline and 5‐hydroxytryptamine transporters in rat and human neocortical synaptosomes*

Abstract: Background and purpose:Although the amino acid sequences of rat and human 5-hydroxytryptamine (5-HT) and noradrenaline (NA) transporters (i.e. SERT and NET) are highly homologous, species differences exist in the inhibitory effects of drugs acting at these transporters. Therefore, comparison of the potencies of drugs acting at SERT and NET in native human and rat neocortex may serve to more accurately predict their clinical profile. Experimental approach: Synaptosomes prepared from fresh human and rat neocorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
2
11
0
1
Order By: Relevance
“…1 is almost the same as the order of K i values for SERT, as previously reported (Bolden-Watson and Richelson, 1993;Thomas et al, 1987). Among SNRIs, there seems to be a correlation between the optimal concentration and K i values for SERT (Mantovani et al, 2009;Bolden-Watson and Richelson, 1993), indicating that an inhibition of SERT is required to cause the augmentation of 5-HT release. To our knowledge, this is the first in vitro report that compares the effects of a number of antidepressant classes on extracellular 5-HT levels, especially after chronic exposure to these agents.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…1 is almost the same as the order of K i values for SERT, as previously reported (Bolden-Watson and Richelson, 1993;Thomas et al, 1987). Among SNRIs, there seems to be a correlation between the optimal concentration and K i values for SERT (Mantovani et al, 2009;Bolden-Watson and Richelson, 1993), indicating that an inhibition of SERT is required to cause the augmentation of 5-HT release. To our knowledge, this is the first in vitro report that compares the effects of a number of antidepressant classes on extracellular 5-HT levels, especially after chronic exposure to these agents.…”
Section: Discussionsupporting
confidence: 75%
“…Because SSRIs, SNRIs, and TCAs commonly block SERT (Mantovani et al, 2009;Vaishnavi et al, 2004), this result is likely due to an acute inhibition of 5-HT reuptake by the blockade of the transporter. In vivo microdialysis studies have demonstrated that acute administration of SSRIs, SNRIs, or TCAs elicits a pronounced increase in 5-HT levels in the raphe, prefrontal cortex, striatum, hypothalamus and hippocampus (Bel and Artigas, 1999;Gartside et al, 1995;Invernizzi et al, 1997;Matos et al, 1990).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We also point out that the serotonin terminals or transporter (SERT) can affect LID severity in preclinical models Eskow et al, 2007;Bishop et al, 2012). However, chronic DMI is not reported to alter SERT expression or function (Hyttel, 1994;Mantovani et al, 2009), thus making it unlikely that changes in SERT expression or SERT-mediated uptake are associated with our behavioral observations. From a clinical perspective, this leads to questions as to whether an antidepressant with NET affinity could produce, hasten the onset of, or worsen the severity of LID, given the prevalence of PD-related depression and that depression commonly precedes motor manifestations (Burn, 2002;Aarsland et al, 2012;Brichta et al, 2013).…”
Section: Norepinephrine Transporter and L-dopa Dyskinesiamentioning
confidence: 97%